(untitled) (Epidemiology, Biostatistics, and Public Health, 2022)
Background. Given rapid advances in genomics, continuing medical education of medical doctors (MDs) is crucial for appropriate integration of human genome discoveries into healthcare and disease prevention. This work presents a systematic review of educational interventions aimed at improving genomic competency in non‐geneticist MDs, with consideration of how outcomes are affected by intervention type (face-to-face learning, distance learning, decision aids and information provision). Methods. We performed a systematic search of MEDLINE, ISI Web of Science, and SCOPUS databases for the relevant studies on educational interventions and genomic competency, published in English language between January, 1st, 2001 and March, 31th, 2017. In order to synthesize the results of the eligible studies, we evaluated the effect of education on knowledge, management and confidence, and we compared the outcomes between different intervention types. Results. We included sixteen studies including different educational interventions. The majority of studies reported significant effects on at least one component of genomic competency. When the improvement in clinical application of genomic knowledge was evaluated, moderate or null effect has been reported for the different intervention types. Conclusions. The majority of studies included reported a positive impact of genomic education on non‐geneticist MDs genomic competency. However, no clear conclusion can be drawn given the heterogeneity of the studies in terms of methods, intervention types and outcome measurements. Future studies considering effectiveness of interventions with a focus on long-term outcomes are recommended.